Training as Part of Capacity Building : Report on IMF Training During 2007. (Policy Papers; Policy Paper ;, 2008)
This Report provides statistical detail on IMF training for member country officials during calendar year 2007. Section I describes the distribution of training by provider, venue, and region. Section II presents information on the courses delivered through the INS program and the distribution of that training by curriculum area. Drawing on the recently integrated database on IMF training (Box 1), it also lists the courses that IMF departments and the regional technical assistance centers delivered outside the INS program.